Ulkomaalaistaustaisten sairaanhoitajaopiskelijoiden käsityksiä terveydestä osana sairaanhoitajan työtä : fenomenografinen haastattelututkimus - Lankinen-Lifländer, Merja (2024)
The conception of health forms the basis for both healthcare and nursing work, on which the nursing profession and the functioning of the healthcare system are based. The conception of health influences the nursing care provided by nurses and nursing students and their handling of health issues with patients. Due to different cultural backgrounds, the conceptions of health of foreign-born nursing students may differ from those of the host country's healthcare system. It is important to understand the conceptions of health on which foreign-born nursing students base their actions and upon which they build their understanding of both the healthcare system and nursing. There is little qualitative research on the conceptions of health among nursing students.